Penerapan Model Pembelajaran Kooperatif “Metode Berpikir dan Berbagi (think pair and share method)” untuk Meningkatkan Hasil Belajar pada Mata Pelajaran Perencanaan Bisnis Konstruksi dan Properti Siswa Kelas XII BKP2 SMKN 2 Karang Baru - Partik (Medan Resource Center, 2022)
This study aims to: (1) find out the implementation of the Think Pair and Share Method in improving student learning outcomes for class XII BKP2 SMK Negeri 2 Karang Baru, (2) find out how effective the application of the Think Pair and Share Method is in improving student learning outcomes in class XII BKP2 SMK Negeri 2 Karang Baru. This research is qualitative in nature, taking place at SMK Negeri 2 Karang Baru for the Academic Year 2021/2022. While this type of research is Classroom Action Research (CAR). The research subjects were students of class XII BKP2 SMK Negeri 2 Karang Baru, totaling 20 people consisting of 12 female students and 8 male students. Collecting data using observation sheets, documentation, pre-test, post-test and evaluation question sheets. The data analysis stage is carried out by collecting data that has been obtained and then analyzing it with theories and concepts that are general in nature and related to facts to correct or investigate the problem. The research activities include planning (Planning), action (Action), observation (Observing), and reflection (Reflecting). The results of this study indicate two main conclusions: the implementation of this classroom action research was carried out in two cycles, each cycle consisting of two meetings. (2) after the implementation of the Think Pair and Share Method with a varied and not monotonous exercise model in the Construction and Property Business Planning (RBKP) learning, student learning outcomes have increased. This can be seen in the acquisition of test and evaluation scores in the first cycle which increased from 30% to 15% and in the second cycle it reached 85%. From this increase, it can be said that the application of the Think Pair and Share Method is very effective in improving students' learning outcomes of Construction and Property Business Planning.